Hematological parameters of newborns from diabetic mothers in Gandhi memorial hospital, Addis Ababa, Ethiopia - Eden Zinabu; Mikias Negash; Yitagesu Goshu; Tadiyos Kebede; Amanuel Kelem; Aster Tsegaye (PLoS ONE, 2025)
Background Diabetes mellitus during pregnancy can significantly affect a newborn’s hematological profile. However, the hematological profiles among newborns of diabetic mothers and their clinical and prognostic implications are not well explored. Therefore, this study aimed to determine hematological parameters of newborns from diabetic mothers in Gandhi Memorial Hospital, Addis Ababa, Ethiopia, 2024. Methods A comparative cross-sectional study was carried out at Gandhi Memorial Hospital from March to May 2024. A total of 196 newborns -98 from diabetic mothers and 98 from apparently healthy mothers—were conveniently enrolled in the study. A hematological profile test was assayed using a Sysmex XN-550 analyzer from the whole blood of mothers and cord blood of newborns collected in EDTA. Glucose was measured using a Cobas C311 analyzer from serum collected using SST test tube. Data was entered and analyzed using SPSS version 26, with descriptive statistics, proportions, and independent t-tests. A P-value of less than 0.05 was considered statistically significant. Results The study found that the mean ± SD value of red blood cell count was 4.87 ± 0.68 vs 3.33 ± 0.98 x1012/L (P < 0.001), hemoglobin 17.48 ± 2.69 vs 12.08 ± 3.48 g/dL (P < 0.001), hematocrit 49.83 ± 7.47 vs 36.13 ± 8.97% (P < 0.001), red cell distribution width 18.35 ± 2.68 vs 17.27 ± 1.92% (P < 0.001), platelet distribution width 12.26 ± 1.80 vs 11.69 ± 1.76% (P = 0.028), and platelet large cell ratio was 26.05 ± 5.27 vs 24.07 ± 2.21% (P = 0.001) were significantly higher in newborns born to diabetic mothers compared to controls. Polycythemia was seen in large numbers in newborns born to diabetic mothers (56.1%, 55/98 vs 1%, 1/98). On the other hand, the platelet count and PCT values were significantly lower in newborns from diabetic mothers than controls, with a mean value of 239.69 ± 92.52 (103/µL) and 0.24 ± 0.09 (%), respectively, with a P value < 0.001. Conclusion The hematological profile shows a significant difference among newborns from mothers with diabetes and apparently healthy mothers. Therefore, it is better to consider hematological parameters as a screening tool for early detection of hematological complications in newborns from diabetic mothers, and this screening should be encouraged.